O lúdico em Química : jogos e atividades aplicados ao ensino de Química - Soares, Márlon Herbert Flora Barbosa (2004)
In this work games and ludic activities are applied to chemistry teaching. In the introduction, the constructivism aspects of the theories of cognitive development are presented. Then, the ideas and theories of both ludic activities and games are considered based on its philosophic, pedagogic and social aspects. Is also proposed four interaction levels between the games and the students. In the first interaction level, the games are utilized to demonstrate an aparent reality by means of a simulation. In the second interaction level, there is a presence of game, in the sense of a competition where there are losers and winners, using a boardgame. In the third interaction level it is conceived the handling of the game by the player, and new games, new toys and new rules will result. In the fourth interaction level comics magazines are used to teach chemistry. Rules, advantages and disadvantages of using games in chemistry teaching are showed and discussed. After that, the games are evaluated based on questions and interviews with both teachers and students. The games are an excellent alternative in the classroom, raising the students interest and, as a result, their motivation. Almost of 100% of the students use to get involved in the games activities in the classroom. As a result, a better discipline is observed. Both students and teachers interact by themselves through the games leading to a improved sociability and cooperation by the players. So, the games cause the cognitive development and it is not a consequence of it.